Mental Healthcare in Postwar Greece, c. 1950–1970 - Kritsotaki, Despo (The Historical Review/La Revue Historique, 2021)
While mental health experts and government officials all over Europe and North America were concerned about the increase in mental troubles and hospitalised patients after World War II, in Greece the mental health system entered a phase of development: between 1950 and 1970 traditional intramural institutions expanded, and alternative extramural services and prevention and aftercare programmes were introduced. This article analyses the sum of these mental healthcare strategies, at the central, local, public and private levels, highlighting the growing public and private demands for mental healthcare, the interplay between the public and private sector, and the inadequacy of these policies in meeting the needs of the population in quality services for the care and cure of the mentally ill.